Design of MDIs for Type 1 Diabetes Treatment via Rolling Horizon Cardinality-Constrained Optimisation. Issue 1 (July 2017) - Carrasco, Diego S.; Matthews, Aaron D.; Goodwin, Graham C.; Delgado, Ramón A.; Medioli, Adrian M.
Abstract: Recent results on cardinality constrained optimisation are used to obtain an optimised Multiple Daily Injection (MDI) insulin regimen for Type 1 Diabetes patients. The optimisation is implemented in a rolling horizon fashion to account for unannounced events. A blood glucose model is described and an algorithm developed to illustrate the aforementioned strategy. The impact of varying the number of allowable injections in a given day is also studied. Real patient data is used to obtain the models and simulation results are included.